Computed Tomography Measurement of Inferior Turbinate in Asymptomatic Adult - El-Anwar,Mohammad Waheed (2017)
Abstract Introduction The inferior turbinate (IT) is the most susceptible turbinate to enlargement causing nasal obstruction. The common belief ascribes most of the enlargement of the IT to mucosal elements. Objective This study aimed to investigate the detailed computed tomography (CT) measurement of the IT in asymptomatic adult by determining the thickness of both the non-bony (mucosa) and bony parts and their relation to nasal air space in different related areas of the nose. Methods We included in the study paranasal CT scans of 108 individuals (216 IT) that had no paranasal pathology. We acquired axial images with multiplanar reformates to obtain delicate details in coronal and sagittal planes for all subjects. We took separate measurements of the thickness of themedialmucosa, bones, and lateralmucosa of the IT on the anterior and posterior portions of ITs. We also measured the air space of the nasal cavity between the septum and IT anteriorly and posteriorly. Results The difference in the air space between nasal septum, anterior and posterior ends of IT was extremely statistically significant (P < 0.0001). The thickness of the medial mucosa was extremely significantly more than the lateral mucosa width (P < 0.0001). There was no significant difference in length of IT at both sides (p = 0.5781). Conclusion The detailed CT measurement of the IT in normal adult is an easy and novel measurement. This study lays the foundation for CT measurement of IT for further work that can describe changes in IT measures after turbinate surgery.